Changes in dream recall frequency, nightmare frequency, and lucid dream frequency over a 3-year period - Schredl, Michael; Göritz, Anja (Dreaming, 2015)
Cross-sectional studies indicate that dream recall frequency declines with age; longitudinal studies, however, are scarce. The present data from 2 online dream studies in the same panel carried out independently (N = 1,340 completed both surveys) indicate that there is an overall decline in dream recall frequency, nightmare frequency, and lucid dreaming frequency, even though for the majority of the sample the 3 variables remained quite stable over this time interval. The reasons for this decline are yet poorly understood. Future longitudinal studies should include cognitive measures (visual memory), personality measures (thin boundaries), sleep parameters, stress measures, and attitude toward dreams scales to test whether changes in these measures might explain the changes in the recall measures.